Long terms results of surgical therapy on strabismus - Cheleva, Vesna; Popovski T; Antova M; Bosnjakovska S (My University, 1995)
This study deals with a comparative analysis of the postoperative results in the treatment of infantile constant esotropia by means of tenotomy and partial myotomy and other surgical approach (recession, resection and elongation of the ocular muscles). The aim of the study was to confirm the advantage of partial tenotomy and myotomy in the surgery of strabismus. The experiences of many years and the obtained results in the application of partial tenotomy and myotomy on strabismus with long lasting effects.
Keywords: recession of eye muscle; resection of eye muscle; elongation of eye muscle